Anti-apoptotic Actions of Allopregnanolone and Ganaxolone Mediated Through Membrane Progesterone Receptors (PAQRs) in Neuronal Cells - Thomas, Peter; Pang, Yefei (Frontiers in Endocrinology, 2020)
The neurosteroids progesterone and allopregnanolone regulate numerous neuroprotective functions in neural tissues including inhibition of epileptic seizures and cell death. Many of progesterone’s actions are mediated through the nuclear progesterone receptor (PR), while allopregnanolone is widely considered to be devoid of hormonal activity and instead acts through modulation of GABA-A receptor activity. However, allopregnanolone can also exert hormonal actions in neuronal cells through binding and activating membrane progesterone receptors (mPRs) belonging to the progestin adipoQ receptor (PAQR) family. The distribution and functions of the five mPR subtypes (α, β, γ, δ, ε) in neural tissues are briefly reviewed. mPRδ has the highest binding affinity for allopregnanolone and is highly expressed throughout the human brain. Low concentrations (20nM) of allopregnanolone act through mPRδ to stimulate G protein (Gs)-dependent signaling pathways resulting in reduced cell death and apoptosis in mPRδ-transfected cells. The 3-methylated synthetic analog of allopregnanolone, ganaxolone, is currently undergoing clinical trials as a promising GABA-A receptor-selective antiepileptic drug (AED). New data show that low concentrations (20nM) of ganaxolone also activate mPRδ signaling and exert anti-apoptotic actions through this receptor. Preliminary evidence suggests that ganaxolone can also exert neuroprotective effects by activating inhibitory G protein (Gi)-dependent signaling through mPRα and/or mPRβ in neuronal cells. The results indicate that mPRs are likely intermediaries in multiple actions of natural and synthetic neurosteroids in the brain. Potential off-target effects of ganaxolone through activation of mPRs in patients receiving long-term treatment for epilepsy and other disorders should be considered and warrant further investigation.